A Study on the Role of Open Education Faculty, the Leader of Distance Learning in Turkey, in Higher Education and its Educational-Social Dynamics - (:unkn) unknown (IGI GLOBAL, 2013)
The distance learning method has changed the conception of classical education and training. In Turkey the distance learning mission has been undertaken by Anadolu University Open Education Faculty (OEF). Therefore, the presence of OEF in higher education has been considered as the need and demand for higher education through distance learning system. However, studying the state's OEF move a demand is not sufficient for an integral analysis. The economic and political structure in the period when OEF was integrated into the education system was critical. In this context, there are significant social dynamics underlying the foundation of OEF as well. In this study, the differences between the distance learning experience in Turkey and other countries are analyzed. Besides the role and share of the OEF in higher education in Turkey is discussed and the socioeconomic reasons of the foundation of the OEF, as specified above, are studied within the framework of the background of the state's educational move. Finally, the positive and negative views of the individuals on the OEF are presented in the study and suggestions are made in this framework.